THE INFLUENCE OF ORGANIZATIONAL CULTUREN AND LEADERSHIP STYLE ON EMPLOYEE WORK DISCIPLINE AT PT TELKOM WITEL SEMARANG - Alfin Mulia Ramadani; Rara Ririn BudiUtaminingtyas; Luqman Khakim (JOBS (Jurnal Of Business Studies), 2018)
The purpose of this research is to analyze the influence of organizational culture and leadership style toward employee work discipline. Collecting data in this research using questionnaries that distributed to 60 employees of PT Telkom Indonesia. The analysis technique is using multiple linear regression. The results of the analyze show that the regression equation Y=3.39440.509x1+0.524x2. In addition, the F test result of 59,89 was bigger than F table it was 2.77. The T test results of the variables organizational culture and leadership style was bigger than t table and has a significance less than level significance that is 0.05. Therefore, it can be concluded the independent variable organizational culture(x1) and leadership style (x2) has a positive dan significant influence toward employee work discipline (y) both partially and simultaneously. The most influence variable is leadership style (x2) with highest regression coefficient is 0.524. The result of the coeficient of determination (R Square) shows that 0.67 of 67% of independen variable are organizational culture and leadership style. Based on the analysis leadership style became the most influential variable, Therefore this study suggests applying a more assertive leadership style to employees of PT Telkom Witel Semarang.